The Influence of Excellent Service and Effective Communication on Customer Loyalty at Excelso Vitka Point Tiban Batam - Zaein, Heryatul Azizah; Rais, Syafruddin (Jurnal Indonesia Sosial Sains, 2024)
This research discusses the effect of excellent service and effective communication on customer loyalty at Excelso Vitka Point Tiban Batam, with increasing business competition in the food and beverage industry, customer loyalty is one of the keys to the success and sustainability of the company. The purpose of this study was to determine the effect of Excellent Service (X1) and Effective Communication (X2) on Customer Loyalty (Y) at Excelso Vitka Point Tiban Batam, the data analysis method used in this study is multiple linear regression, by distributing questionnaires to 91 respondents who have made purchases at Excelso Vitka Point Tiban Batam with accidental sampling method, testing the research hypothesis using SPSS. The results of this study suggest that pasrial excellent service has a positive and significant effect on customer loyalty (sig <α), effective communication has a positive but insignificant effect on customer loyalty (sig>α), excellent service and effective communication have a positive and significant effect simultaneously (sig<α).